Predicting COVID-19 vaccination intention using protection motivation theory and conspiracy beliefs. Issue 42 (8th October 2021) - Eberhardt, Judith; Ling, Jonathan
Highlights: Intention to get the COVID-19 vaccine can be predicted with Protection Motivation Theory constructs. Greater conspiracy beliefs are associated with lower COVID-19 vaccination intention. Unvaccinated individuals tend to have greater conspiracy beliefs than vaccinated individuals. Abstract: Background: While COVID-19 vaccine uptake has been encouraging overall, some individuals are either hesitant towards, or refuse, the vaccine. Protection Motivation Theory (PMT) has been applied to influenza vaccine acceptance, but there is a lack of research applying PMT to COVID-19 vaccine acceptance. Additionally, prior research has suggested that coronavirus conspiracy beliefs and demographic factors may play a role in attitudes towards the vaccine. This study aimed to predict COVID-19 vaccination intention using PMT, coronavirus conspiracy beliefs, and demographic factors. Furthermore, vaccinated and unvaccinated individuals were compared in relation to their coronavirus conspiracy beliefs. Methods: An online survey was administered to 382 (278 vaccinated, and 104 unvaccinated) individuals in the United Kingdom (77 males, 301 females, one non-binary/third gender, and three unstated). Respondents' mean age was 43.78 ( SD  = 12.58). Results: A hierarchical multiple linear regression was performed in three stages. Initially, four PMT constructs - severity, susceptibility, maladaptive response costs, and self-efficacy - emerged as significant predictors of COVID-19 vaccination intention. The final model accounted for 75% of the variance and retained two significant predictors from PMT - maladaptive response rewards and self-efficacy - alongside coronavirus conspiracy beliefs and age. An independent t -test established that unvaccinated individuals held greater coronavirus conspiracy beliefs than vaccinated ones. Conclusions: Interventions and campaigns addressing COVID-19 vaccine acceptance should employ strategies increasing individuals' perceived severity of COVID-19, perceived susceptibility, and perceived ability to get vaccinated, while decreasing perceived rewards of not getting vaccinated. Additionally, coronavirus conspiracy beliefs should be addressed, as these appear to play a role for some vaccine-hesitant individuals.